STRATEGI KEPALA SEKOLAH PERANGKAPAN DALAM MANAJEMEN PEMBELAJARAN DIGITAL DI SDN 4 BANYURINGIN KABUPATEN KENDAL - Iwan Candra Bachtiar; Soedjono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of technology in education has encouraged schools to adopt digital learning as part of instructional innovation. However, challenges arise when school principals must multitask while ensuring the effectiveness of digital learning implementation. SDN 4 Banyuringin, Kendal Regency, serves as an example of a school that has successfully implemented digital learning management strategies despite these constraints. This study aims to analyze the strategies of a multitasking school principal in managing digital learning at SDN 4 Banyuringin, Kendal Regency. The research employs a qualitative method with a case study approach. The findings indicate that the implementation of digital learning in this school has been effective and positively impacts student learning quality. This success is largely supported by a delegation strategy involving senior teachers who have undergone intensive digital training. These senior teachers serve as mentors for their colleagues, facilitating a smoother adoption of technology in the classroom. Additionally, the use of communication technology, support from the education department, infrastructure readiness, and periodic evaluations have further contributed to the program's success. Increased student engagement, improved comprehension of materials, and enhanced academic achievement serve as key indicators of effective digital learning implementation. The findings of this study can serve as a reference for other schools in developing effective digital learning management strategies.